PORT EFFICIENCY ANALISIS USING DATA DEVELOPMENT ANALYSIS (DEA) METHOD - Pires, Gabriel Campos (2017)
This work presents a study of relative efficiency of some ports using the Data Development Analysis (DEA). During the work, some ports chosen for the study are presented, as well as defined variables, inputs and outputs for modeling, and the mathematic model based on linear programming. Next, the relative efficiency obtained in each port is presented, and a comparison among the ports is carried out from the benchmarking, proposing changes in order to optimize port operations.